Metallic Properties of a Natural Fibres Reinforced Composite-Bamboo - Jindal, U. C. (Indian Forester, 1984)
From the very beginning, bamboo is being used for many industrial, commercial and structural applications, yet the literature on mechanical behaviour of bamboo Is not much. In the present work, bamboo specimens have been tested under torsion, tension and impact. The effect of protective coating of Araldlte on bamboo specimens for the prevention of environ-mental attack also bas been investigated. It was observed that the atrength and stiffness of bamboo are maximum along the fibres and minimum transverse to the fibres. The tensile and impact strength of bamboo specimens Increase If these are soaked in Araldile mixture for two days. The ultimate tensile strength of bamboo specimen is equal to the yield strength of mild steel. But the notch Impact strength and torsional shear strength of bamboo are much less in comparison to those of mild steel. The mechanical behaviour and mode of fracture of bamboo specimens under various types of loading are similar to those of artificially developed fibre-reinforced composites.